2007
DOI: 10.1002/dvdy.21181
|View full text |Cite
|
Sign up to set email alerts
|

Novel genes involved in Ciona intestinalis embryogenesis: Characterization of gene knockdown embryos

Abstract: The sequenced genome of the urochordate ascidian Ciona intestinalis contains nearly 2,500 genes that have vertebrate homologues, but their functions are as yet unknown. To identify novel genes involved in early chordates embryogenesis, we previously screened 200 Ciona genes by knockdown experiments using specific morpholino oligonucleotides and found that suppression of the translation of 40 genes caused embryonic defects (Yamada et al.[2003] Development 130:6485-6495). We have since examined an additional 304… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Cluster 5 cells clustered closely with dorsolateral brain neurons (Cluster 3) and also expressed Rlbp1, but they showed little expression of differentiated neuronal markers (Supplemental Table 1, sheet 5). Expression of markers like Aquaporin 8 (Hamada et al, 2007), Zeb (also known as Zinc Finger (C2H2)-33 or Ci-ZF266) (Imai et al, 2004), and Gonadotropin-releasing hormone.b (Gnrh.b, previously called GnRH2) Kusakabe et al, 2012) (Fig 2C), indicated that these might be the so-called ependymal cells lining the sensory or brain vesicle, a specialized fluid-filled cavity important for the function of associated sensory organs such as the ocellus and otolith (Tsuda et al, 2003b). In addition to forming the epithelium that lines the brain vesicle and other parts of the neural tube (Katz, 1983;Mackie and Bone, 1976), these cells also function as neural progenitors that give rise to the adult CNS after metamorphosis .…”
Section: Resultsmentioning
confidence: 99%
“…Cluster 5 cells clustered closely with dorsolateral brain neurons (Cluster 3) and also expressed Rlbp1, but they showed little expression of differentiated neuronal markers (Supplemental Table 1, sheet 5). Expression of markers like Aquaporin 8 (Hamada et al, 2007), Zeb (also known as Zinc Finger (C2H2)-33 or Ci-ZF266) (Imai et al, 2004), and Gonadotropin-releasing hormone.b (Gnrh.b, previously called GnRH2) Kusakabe et al, 2012) (Fig 2C), indicated that these might be the so-called ependymal cells lining the sensory or brain vesicle, a specialized fluid-filled cavity important for the function of associated sensory organs such as the ocellus and otolith (Tsuda et al, 2003b). In addition to forming the epithelium that lines the brain vesicle and other parts of the neural tube (Katz, 1983;Mackie and Bone, 1976), these cells also function as neural progenitors that give rise to the adult CNS after metamorphosis .…”
Section: Resultsmentioning
confidence: 99%
“…Morphological phenotypes were obtained following loss of function of 221 of these genes. These phenotypes were described textually and with a picture (Yamada et al 2003;Hamada et al 2007). In addition, ANISEED describes the transcriptional consequences of gene loss-or gain-of-function of 94 genes with developmental phenotypes, mostly transcription factors, signaling ligands, or genes with no previously known function.…”
Section: Description Of Expression Data In Wild-type and Experimentalmentioning
confidence: 99%
“… Extracting knowledge from scientific articles. After analyzing the article (for example, the article from Hamada et al , ), the biocurator extracts and converts data thanks to the ontologies. He can also refine the annotation using his expertise and the pictures from the article (e.g., “tailbud stage” becomes “mid‐tailbud” and expression in “endoderm and nervous system” becomes “head endoderm and anterior sensory vesicle”).…”
Section: The Role Of Biocurationmentioning
confidence: 99%
“…Annotating data: Annotating means connecting an entity to broader concepts by attaching a comment, explanation, or tag, defined by standards. This mark-up of data to add value is the basis of data Hamada et al, 2007), the biocurator extracts and converts data thanks to the ontologies. He can also refine the annotation using his expertise and the pictures from the article (e.g., "tailbud stage" becomes "mid-tailbud" and expression in "endoderm and nervous system" becomes "head endoderm and anterior sensory vesicle").…”
Section: Developing and Managing Annotation Standardsmentioning
confidence: 99%